Cross sectional survey of multicentre clinical databases in the United Kingdom. Issue 7454 (17th June 2004) - Black, Nick; Barker, Marian; Payne, Mary
Abstract: Objectives To describe the multicentre clinical databases that exist in the United Kingdom, to report on their quality, to explore which organisational and managerial features are associated with high quality, and to make recommendations for improvements. Design Cross sectional survey, with interviews with database custodians and search of electronic bibliographic database (PubMed). Studies reviewed 105 clinical databases across the United Kingdom. Results Clinical databases existed in all areas of health care, but their distribution was uneven—cancer and surgery were better covered than mental health and obstetrics. They varied greatly in age, size, growth rate, and geographical areas covered. Their scope (and thus their potential uses) and the quality of the data collected also varied. The latter was not associated with any organisational characteristics. Despite impressive achievements, many faced substantial financial uncertainty. Considerable scope existed for improvements: greater use of nationally approved codes; more support from relevant professional organisations; greater involvement by nurses, allied health professionals, managers, and laypeople in database management teams; and more attention to data security and ensuring patient confidentiality. With some notable exceptions, the audit and research potential of most databases had not been realised: half the databases had each produced only four or fewer peer reviewed research articles. Conclusions At least one clinical database support unit is needed in the United Kingdom to provide assistance in organisation and management, information technology, epidemiology, and statistics. Without such an initiative, the variable picture of databases reported here is likely to persist and their potential not be realised.